The Law of Adoption of a Child in the Womb and Its Status - Panjaitan, Rizky Syahputra Azhar; Purba, Zainal Arifin (Institut Agama Islam Negeri Kendari, 2025)
There is a significant lack of research that specifically addresses the legal and social implications of adopting children while they are still in the womb, particularly within the intersection of Islamic Law, positive Law, and local customs in Indonesia. This study explores the Law of adoption of children in the womb and their status. Researchers conducted research in the Sei Merbau District, where there is a phenomenon of adoption of children in the womb in several communities. The method used in this study is a qualitative method using an interview approach with the research respondents. The findings of this study are that there has been adoption and change in the status of children in the womb in Sei Merbau District, Tanjungbalai. In the analysis of Islamic Law, inconsistencies were found, where the adoptive parents mixed up the nasab by using their names as the biological parents of the adopted child. This activity is prohibited because it can change the Law from the adoption of a child who was originally “mubah” to “haram” due to the emphasis on the integrity of nasab. Meanwhile, in Positive Law, it was found that the adoption process did not go through a valid court and that there was an unauthorised change in civil status documents. This research highlights the urgent need for a clear and integrated legal framework to regulate the adoption of unborn children, ensuring the protection of the child’s rights and the consistency of legal practices with religious and national laws. This study reveals legal loopholes in the adoption of children in the womb and the importance of integrating Islamic law, positive law, and customary law in Indonesia.Keywords: Adoption, Status, Islamic Law, Positive Law